Humor and social norms on social media: When bible verses or memes mobilize Christians for humanitarian collective actionOpen Science Framework - Hedy Greijdanus; Willem van de Wetering; Casper Roos (Acta Psychologica, 2025)
Group members' decisions on whether or not to become actively involved in collective action are often guided by social norms regarding both action and inaction. Previous research tentatively suggests that humor may be a means to mock inaction norms and thereby increase mobilization for collective action. The current research investigates Christian student association members' group norms regarding humanitarian collective action. While prescriptive ingroup norms advocate such prosocial behavior, descriptive ingroup norms indicate reluctance to engage in humanitarian action. Members from nation-wide chapters of Christian student association throughout The Netherlands (N = 248) saw a social media post mobilizing for a foodbank action by the association. This mobilizing call for action was accompanied either with bible verses as prescriptive norms to partake in humanitarian collective action or with humorous internet memes mocking descriptive norms of reluctance to engage in collective action. A questionnaire measured 1) their collective action intentions (to participate in the advertised action, outreach actions, and humanitarian action), 2) their affective reactions to the social media post (inspired, amused, angry), 3) activist burnout symptoms, and 4) perceived group, participative, and individual efficacy. Stronger social identification predicted feeling more inspired by the social media call for action as well as increased humanitarian action intentions. This classical discrepancy between high and low social identifiers decreased when the call to action displayed humorous memes mocking descriptive inaction norms instead of bible verses as prescriptive action norms. These findings shed light on alternative routes to mobilize high and low Christian identifiers for humanitarian collective action.